Effect of Growth Promoter (Rapid Growth) as a Supplementation on The Growth Performance Feed Utilization of Monosex Tilapia - Islam, AFM M; Zaman, MT; Rahman, MM (Journal of Environmental Science and Natural Resources, 2015)
The present study was conducted in farmers ponds at field level of Muktagachha upazilla to find out the effect of growth promoter on growth performance and feed utilization of monosex Tilapia fish. Growth promoter was used in the experimental cultured farm. This growth enhancing aqua drugs was used in feeds of Tilapia. The results indicated that the growth promoter was the best treatment which significantly (P ? 0.05) increased of all growth performances (final weight, AWG, ADG and SGR), improved FCR, and best economic efficiency. It was clearly observed that there were distinct impacts of growth promoter on fish growth and production. In the present study water quality parameters were within the suitable range. Production of Tilapia i.e. 4650 kg/acre in promoter treated ponds whereas 3666 kg/acre in non treated ponds were recorded. Food conversion ratio (FCR) was 1.70 and 1.38 were found in the controlled and treated pond respectively. Clinically the treated fishes did not show any remarkable changes. There were no adverse effects on water quality criteria among all experimental treatments. It could be concluded that the inclusion of the commercial probiotic Rapid Grow at a level of 0.05mg Kg-1 diet at stocking density rate of 250 fish/ decimal of mono-sex Tilapia O. niloticus is useful to get the best fish performance with friendly effects on the environment. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22152 J. Environ. Sci. & Natural Resources, 7(1): 99-104 2014